2008
DOI: 10.1007/s12010-008-8401-2
|View full text |Cite
|
Sign up to set email alerts
|

Callus Induction and Plant Regeneration from Different Explants of Actinidia deliciosa

Abstract: In this study, an efficient procedure was developed for callus induction and regeneration of kiwifruit (Actinidia deliciosa) using different organs of shoots developed under in vitro conditions. Effects of explants source and media (M(1), 1.0 mg l(-1) BA + 2.0 mg l(-1) 2,4-D-M(2), 1.0 mg l(-1) NAA + 2.0 mg l(-1) 2,4-D) on initiation of callus were examined in order to obtain callus for organogenesis. The best callus for plant regeneration was obtained from leaf explants on Murashige and Skoog's medium (MS) sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Also regression analyses indicated that higher concentrations of BAP had an inhibitory effect on proliferation. Our results are in agreement with those of Akbas et al [39] on Amygdalus communis L. that the decrease of proliferation rate, length of micro-shoot and an increase of callus end of micro-shoot are due to the strong concentrations of BAP which inhibit them.…”
Section: Discussionsupporting
confidence: 94%
“…Also regression analyses indicated that higher concentrations of BAP had an inhibitory effect on proliferation. Our results are in agreement with those of Akbas et al [39] on Amygdalus communis L. that the decrease of proliferation rate, length of micro-shoot and an increase of callus end of micro-shoot are due to the strong concentrations of BAP which inhibit them.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, at day 45 of culture, a CG rate of 3.8-4.0 was detected for all explant types (Figure 3b) suggesting that callus production in Aster is species and genotype dependent (Cammareri et al 2001). In plant species such as Aster tripolium L. (Uno et al 2009), Saussurea obvallata (Dhar & Joshi 2005) and Actinidia deliciosa (Akbas et al 2009) profuse callus production and proliferation were obtained using leaf explants. On the contrary, for Changium smyrnioides, petioles were the best explants for obtaining callus culture (Jiang et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Many PGRs have been used in tissue culture of Actinidia species, and their effects have varied depending on the species and explant type used (Mezzetti et al 1991a(Mezzetti et al , 1991bInfante et al 1994;Akbas et al 2009;Moncalean et al 2009). …”
Section: Discussionmentioning
confidence: 99%